Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1161/01.str.31.6.1299
|View full text |Cite|
|
Sign up to set email alerts
|

Age-Dependent Association of Apolipoprotein E Genotypes With Stroke Subtypes in a Japanese Rural Population

Abstract: Background and Purpose-The association between apolipoprotein E (apoE) polymorphisms and stroke has been controversial. These controversies may be due to inaccurate classification of stroke and differences in age ranges. We investigated the association between apoE genotypes and stroke subtypes (confirmed by CT or MRI findings) by case-control study in a Japanese rural population. Methods-First-ever-stroke patients (nϭ322; cerebral infarction, nϭ201, intracerebral hemorrhage, nϭ84, and subarachnoid hemorrhage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 68 publications
4
64
3
Order By: Relevance
“…It can be argued that the E3=4 genotype is a protective factor for ischemic stroke in the investigated population. This data is in conflict with studies undertaken on other populations, however, where the e2 allele occurred as a protective factor (Kokubo et al, 2000;Ferrucci et al, 1997), or the E3=3 genotype occurred as a protective factor (Margaglione et al, 1998;Couderc et al, 1993). Likewise, e4 allele frequency was found to be decreased in the ischemic group compared to controls.…”
contrasting
confidence: 81%
See 1 more Smart Citation
“…It can be argued that the E3=4 genotype is a protective factor for ischemic stroke in the investigated population. This data is in conflict with studies undertaken on other populations, however, where the e2 allele occurred as a protective factor (Kokubo et al, 2000;Ferrucci et al, 1997), or the E3=3 genotype occurred as a protective factor (Margaglione et al, 1998;Couderc et al, 1993). Likewise, e4 allele frequency was found to be decreased in the ischemic group compared to controls.…”
contrasting
confidence: 81%
“…A less robust cytoskeleton, oxidative damage, increased edema, and poor mobilization of cholesterol and lipids are all putative mechanisms by which apo E could affect acute stroke. Studies-to-date have produced apparently conflicting results on the influence of APOE alleles on predisposition to ischemic stroke Strittmatter et al, 1993;Davignon et al, 1998;Stengard et al, 1995;Kokubo et al, 2000;Margaglione et al, 1998;Kessler et al, 1997). In small case-control or cross-sectional studies, e2 (Couderc et al, 1993), e4 (PedroBotet et al, 1992), or both alleles (Kuusisto et al, 1995) have been significantly overrepresented, while others have found no influence of APOE polymorphisms (Coria et al, 1995;Basun et al, 1996;Mahieux et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…21 The relevant allele frequencies in 100 cases were ⑀Ϫ2ϭ4%, ⑀Ϫ3ϭ85%, and ⑀Ϫ4ϭ11%, which were not different from 100 control subjects (Table 5) and the Japanese general population. 22 Six genotype frequencies were ⑀Ϫ2/⑀Ϫ2ϭ0%, ⑀Ϫ2/⑀Ϫ3ϭ7.0%, ⑀Ϫ2/⑀Ϫ4ϭ0.5%, ⑀Ϫ3/⑀Ϫ3ϭ69.9%, ⑀Ϫ3/ ⑀Ϫ4ϭ20.6%, and ⑀Ϫ4/⑀Ϫ4ϭ2.0% in cases, being the same in control subjects.…”
Section: Case-control Study For Candidate Genesmentioning
confidence: 78%
“…On the other hand, an epidemiological study among Japanese ranked APOE high as a candidate gene on chromosome 19q13. 21 However, in the case-control study, albeit with very limited numbers of plausible genes, candidate genes including APOE failed to show positive associations with IA. Obviously, LD mapping covering entire regions is required to search for clues to susceptibility genes.…”
Section: Candidate Genesmentioning
confidence: 89%
“…In a study of stroke in a Japanese rural population, Kokubo et al 32 found that, compared with individuals with the APOE e3/e3 genotype, e2 carriers had a 2-fold risk of cerebral infarction. The risk is greater for cortical infarction, but not for lacunar infarction.…”
mentioning
confidence: 99%